Cytopathological findings of primary pulmonary Ewing family of tumors with EWSR1 translocation: A case report. Issue 5 (24th March 2016) - Mizuguchi, Keishi; Minato, Hiroshi; Onishi, Hitomi; Mitani, Yuki; Kawai, Jun
Abstract : Primary pulmonary neoplasms of the Ewing family of tumors (EFT) are extremely rare and usually occur in adolescents or young adults. Only about 40 cases of pulmonary EFT have been reported in English literature, and no cytological studies have been documented. In this report, we describe the cytopathological findings of a primary pulmonary EFT in an elderly patient. A 70‐year‐old man sought care because of a progressing cough and dyspnea. Chest computed tomography revealed a circumscribed mass of 6 cm in the left upper lobe. Fine needle aspiration cytology and core needle biopsy revealed uniform round cell proliferation. The predominant population consisted of cells with thickened nuclear membranes, finely dispersed chromatin, single distinct nucleoli, and indistinct cytoplasm. The other population consisted of smaller cells with darker chromatin. The cytoplasm stained positive for periodic acid–Schiff stain and was digested by diastase. Immunohistochemistry showed positivity for MIC2 (CD99), and focal positivity for neuron specific enolase, synaptophysin, and chromogranin A. Fluorescence in situ hybridization (FISH) revealed EWSR1 translocation. Although rare, pulmonary EFT cannot be disregarded, regardless of age. When two populations of uniform, round cells are observed, immunohistochemistry with MIC2 (CD99) and cytogenetic analysis by reverse transcription polymerase chain reaction or FISH should be considered. Cytological diagnosis may play an important role in the early diagnosis and treatment of pulmonary EFT.